The Image of Nurses and Midwives in Ghana: Patient and Family Perspectives - Lillian Akorfa Ohene; Angela Kwartemaa Acheampong; Gladys Dzansi; Josephine Kyei; Charles Ampong Adjei; Samuel Adjorlolo; Isabella Naana Akyaa Asante; Philomena Woolley; Felix Nyante; Lydia Aziato (SAGE Publishing, 2022)
This study aims to explore the perceptions of patients and family caregivers on the image of nurses and midwives in Ghana. The study adopted a qualitative exploratory descriptive approach. A total of 25 participants were interviewed during data collection. Content and thematic analysis were applied in the data analysis to develop themes. The findings are captured under two major themes that describe the primary influences on participant images of nurses: Thus, (1) nurses' and midwives' attributes with four subthemes; staff appearance, communication strategies and behaviors, work attitudes, and professional competence and (2) patients' status and subthemes were; uneducated poor and educated rich. We conclude that patients and families in Ghana recognize the professional attributes of the nurse and midwife, which reflect in their personality, grooming, communication, competencies, and attitudes. However, low publicity of the professional roles of nurses and midwives may have negative repercussions for their professional image. A policy to perform a regular public audit on the image of the Nurse/Midwife is important for professional advancement.